Evaluating the Impact of Indonesia’s Instagram Influencer Marketing on Influencing Purchase Decision of Their Followers - Daud, Nasreen Anis Putri; Basbeth, Firdaus (Sekolah Tinggi Manajemen IPMI, 2022)
Social media influencers are winning over the internet with their outstanding work and presence. Their opinions have a powerful impact on people, especially on the young generation. We can mark them as a modern phenomenon that has seen a huge increase in cooperation with marketing agencies over recent years. More and more people are following such influencers so that they do not miss out on their content. Brands flock to such influencers for mentions, reviews, and recommendations. Even though influencer marketing is a relatively new strategy, it continues to be a viable solution for marketers who are willing to think outside the box while building relationships with their target market. The aim of the study is to offer a comprehensive reflection on influencer marketing opportunities and determine the impact of influencers on consumer behavior of Generation Y and Z. We wanted to find out whether influencers, who promote products, can attract potential customers and encourage them to purchase, as well as find differences between the given consumers' generations. The analysis is performed using statistics. Thus, this inquiry is also a study of causality. Causal research, alternatively referred to as explanatory study, is used to determine the extent and type of cause-and-effect relationships